Tourism policy and territorial imbalances in Spain (1) - García, Fernando Almeida (Bulletin of Geography. Socio-economic Series, 2013)
This paper aims to analyse Spanish tourism policy and its relation to a series of facts. The research combines an extensive review of the existing studies into the aspects of tourism policy linked to government, geography and economy with an examination of statistical sources. The main issues and findings analysed in this study are highlighted below. Firstly, the evolution of tourism policy of Spain in the last 60 years in relation to the process of national economic development is analysed. Secondly, a limited role of tourism on economic and territorial balance as well as changes in the regional distribution in the supply of hotel accommodation is highlighted. Thirdly, territorial changes related to the supply of hotel accommodation and GDP per capita are discussed. Finally, certain topics are suggested for future debate: tourism and imbalance as well as tourism and development.